A standardized criteria-based progressive shoulder exercise program is effective in managing rotator cuff-related shoulder pain: A prospective cohort study - Judy Chepeha; Anelise Silveira; David Sheps; Charlene Luciak-Corea; Fiona Styles-Tripp; Lauren Beaupre (PLoS ONE, 2025)
Background Non-operative management of patients with rotator cuff related shoulder pain (RCRSP) has been shown to be effective with outcomes similar to operative interventions. Exercise therapy and education are recommended as first-line treatments; however, program content, progression and referral criteria are typically inadequately detailed to be easily reproduced by clinicians. This study evaluated the effectiveness of a well-defined, criteria-based progressive exercise physical therapy (PT) program in patients with rotator cuff related shoulder pain (RCRSP) over a 26-week evaluation period. Methods and findings A longitudinal, prospective cohort study evaluated 143 patients aged 30–65 years with RCRSP. Participants participated in a 12-week in-person and home-exercise shoulder program and were assessed at baseline, 6-weeks, 12-weeks and 26-weeks. Primary outcome measures were pain at rest, at night and with activity. Secondary measures were active range of motion (ROM), strength, and health related quality of life (HRQL) using the Western Ontario Rotator Cuff (WORC) score. Results Significant reductions in pain at rest, at night and with activity (p < 0.001) occurred within six weeks and continued to 26-weeks. Active range of motion (ROM), particularly abduction and external rotation in 90 degrees of abduction, significantly improved between 0- and 6-weeks (p < 0.001) as well as at 12-weeks (p < 0.001) and 26-weeks (p < 0.001). Strength similarly improved, especially between 6- and 12-weeks (p < 0.001). Ongoing improvements were reported at 26-weeks. Finally, the WORC score improved over time, with significant improvements at each measurement point, and clinically important improvements occurring within 12 weeks. Conclusion(s) Utilizing a criteria-based progressive PT program that provided detailed information, including progression criteria and a proven algorithm for referring non-responsive patients for an orthopedic surgical consult was effective in significantly reducing pain, improving active ROM, strength and HRQL in those living with RCRSP.